Effect of non-genetic factors on lactation and reproductive performance of Gir cows (Indian Journal of Animal Production and Management, 2024)
Effect of non-genetic factors viz., with or without calf stimulus at milking i.e., restricted suckling or non suckling, age and body weight of first calvers, parity and season of calving on lactation and reproductive  performance of 194 Gir cows were investigated. Lactation days (LL), total lactation milk yield (TLMY),300-d  milk yield (SLMY), peak yield/day (PY), days to attain peak yield (D-PY), uterine involution time post-partum  (D-UI), post-partum oestrus interval (PPOI) and service period (SP) of farm born Gir females, calving / drying  during April, 2009 to March, 2012 at CBF, Junagadh were analyzed. Over-all LL, TLMY, SLMY, PY, D-PY,  D-UI, PPOI and SP of the Gir cows were 337.62±7.89 days,1838.25±64.94 lit ,1637.87±50.56 lit ,10.29±0.22  lit/day ,58.73±0.65 days, 33.04 ±0.51 days, 94.00±1.34 days and 179.51±3.08 days, respectively. Calf  rearing method, age and body weight of first calvers and season of calving did not influence significantly the  performance traits. However, reproductive performance was significantly (P
Keywords: Association; Gir; Lactation; Non-genetic factors; Reproduction